External evaluation of the Finnish-Swedish Winter navigation R&I programme - Ojala Lauri; Nylander Jan (Traficom, 2025)
In the winter navigation research and operations collaboration, Finland and Sweden are taking on a wide range of common challenges in ice infested seaborn trade and regulatory framework in the northernmost parts of Europe. Achievements from the cooperation have also provided important knowledge and experiences, stimulating public and private operators, shipbuilders and users of maritime logistic resources towards more secure, cost efficient and climate smart solutions. Countries with icy winter conditions in the Baltic Sea as well as the connectivity of EU transport network benefits from progress made in winter navigation research.
The research and innovation cooperation through the Winter Navigation Research Board (WNRB) is based on a joint Swedish - Finnish agreement dating back to 1972. In order to take stock and report on developments the Finnish and Swedish maritime agencies, members of the WNRB and cooperation (Finnish Transport Infrastructure Agency, Finnish Transport and Communications Agency, Swedish Maritime Administration and the Swedish Transport Agency) have decided to evaluate 50 years of research and cooperation.
In their evaluation report, two external and independent evaluators, one from Finland and one from Sweden, have focused their assessment efforts on some main areas. These main areas include the overall governance, organisation and processes, research calls, research quality, research results and their societal impact and the relevance for winter navigation and operational icebreaking services. Furthermore, the evaluators assessed funding arrangements and long-term cooperation in demand driven winter navigation research. The WNRB also requested that the evaluation would present some recommendations on future development as well as the further strengthening of winter navigation research in the light of international developments.
The results of the evaluation will serve as a basis for addressing needs, shortcomings and how to build a more robust winter navigation research among transport authorities in Finland and Sweden for the coming 50 years.